A Perspective on Male Contraceptive Therapeutics of Hydro-ethanol Extract of Seeds of Luffa acutangula (L.) Roxb. in Human and Albino Rat: An In-vitro Meta-Analysis Study (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Traditionally Luffa acutangula (L.) Roxb. has been utilized as an herbal contraceptive. This in-vitro study has been performed to search out the male contraceptive efficacy of hydro-ethanol (60:40) extract of Luffa acutangula (LAHEE) seeds in a dose-specific manner (1, 2, and 4 mg/ml of in-vitro media). The percentages of motile, viable, hypo-osmotic swelled (HOS), and acrosomal intact of human and rat sperms were declined significantly (p<0.05) at the above-mentioned doses of LAHEE-exposed groups against the placebo group. The inhibitory concentration 50% value (IC50) of LAHEE was 2.5 mg/ml in human and 1.2 mg/ml in rat spermatozoa immobilization. The ∆5,3β and 17β hydroxysteroid dehydrogenase (HSD) activities of rat’s testicular tissues were inhibited significantly at p<0.05 in LAHEE-treated groups than the placebo group. Activities of superoxide dismutase (SOD) and catalase were significantly inhibited (p<0.05) along with the significant increment (p<0.05) in the quantity of thiobarbituric acid reactive substances (TBARS) in rat’s testes and epididymis, sperm pellets of humans and rats in LAHEE-treated groups against the placebo group without any significant difference (p>0.05) in above said sensors in the liver and cardiac tissues of rats. The non-toxic nature of LAHEE was indicated by no significant alterations (p>0.05) in the activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) after LAHEE exposure in said tissues of rats. The LC-MS study of LAHEE identified the presence of oleic acid, dihydroquercetin, luteolin-7-glucoside, formononetin, luteolin 8-C-pentoside-6-C-hexoside, pterosin B, boldine and berberine. These findings interpreted that the LAHEE possesses spermiological inhibitory and hypo-testicular activities, which indicate a promising possibility to develop a potent herbal male contraceptive agent from this plant extract.